4CPS-236 The impact of a ward-based pharmacy technician service. (March 2019) - Lynch, E; O'Fynn, J; O'Riordan, C; Bogue, C; Lynch, D; McCarthy, S; Murphy, K
Abstract : Background: Pharmacy technicians have been employed in hospital settings for many years but only recently has the potential for service expansion been explored. There is a paucity of research on the impact of a ward-based pharmacy technician service (WBPTS) in this country. Purpose: To determine the impact of a WBPTS on medicine management systems, patient safety and healthcare costs. Material and methods: Sixteen wards were studied over 8 weeks: four 'intervention' wards (assigned a WBPTS prior to the study) and 12 'control' wards (technicians providing a stock 'top-up' service). The 'intervention' wards comprised mainly medical patients, a WBPTS had been assigned to these wards as they were considered high-activity wards. The control wards comprised both medical and surgical patients. The medication management systems were inspected by the researchers for the presence of excess non-stock medicines and expired medication. Nurses were observed to calculate time taken to complete drug rounds. Patient drug charts were analysed to calculate the duration to pharmacist review of high-risk medications. Nursing staff were surveyed on their opinions of the service. Results: The total value of excess non-stock on intervention wards was €97.51 (mean cost/ward: €24.38) compared with €13, 767.76 on control wards (mean cost/ward: €1, 147.31). Eight expired medications were found on control wards, none were present on intervention wards. The mean time to complete drug rounds on a per-patient basis was 28% lower on intervention wards. The median time to pharmacist review of high-risk medications was shorter on intervention wards (0.67 vs 4.2 days). One-hundred per cent of respondents agreed that the WBPTS should continue. Conclusion: More widespread investment in the WBPTS has the potential to reduce healthcare expenditure due to excess medicines, increase nursing time spent on direct care of patients and reduce the potential for patient harm from high-risk medicines. The current study did not consider the costs associated with WBPTS (e.g. personnel costs, additional time spent by technicians/time saved by nurses) and so further studies should consider the full economic costing of the service. References and/or acknowledgements: 1. Elliott RA, Perera D, O'Leary K. National survey of clinical pharmacy services and pharmacy technician roles for subacute aged-care inpatients. J Pharm Pract Res 2012;42:125–8. No conflict of interest.